Writing Challenges and Strategies in ESP Contexts: Pharmacy Students’ Perception in Higher Education Institutions in Jambi - Silvia, Resi (JURNAL INOVASI EDUKASI, 2024)
Many ESP learners encountered difficulties from the writing process. Students in higher education institution are required to produce essays, which are difficult and may frustrate students. The purpose of this study was to analyse the most difficult aspects of writing faced by pharmacy students studying in a university in Jambi and how those challenges might relate to their writing strategies. This is a survey study to sheds light on the key factors that could cause those difficulties in their point of view. The instrument used was questionnaire to gather the data of this study. The results showed that the most common challenges is related to grammar and sentence structure as well as organization, coherence and cohesion. Others are related to paraphrasing. Another conclusion which can be drawn is the most helpful strategies, form students point of view, are writing an outline/plan for the essay, specific feedback by the teacher, using a dictionary, extensive reading about the topic, examining writing model.